Adaptation and validation of substance use risk profile scale (SURP) for Pakistani population - Farooqi, Rabia; Anam (Journal of the Pakistan Medical Association, 2022)
Objective: To adapt, validate and establish psychometric property of the Substance Use Risk Profile scale for Pakistani population. Method: The cross-sectional study was conducted from May to September 2021 in Lahore, Pakistan, and comprised clinical and non-clinical adult patients following the International Test Commission guidelines for the adaptation and validation of the Substance Use Risk Profile scale. A The scale’s factor structure, internal consistency, content validity, face validity and convergent validity were exained. Confirmatory factor analysis, reliability analysis, and data analysis were done using SPSS 25. Results: Of the 485 subjects, 243(50.1%) were non-clinical and 242(49.9%) were clinical subjects. The overall mean age was 4.68+/-2.3 years (range: 19-58 years). The scale had adequate internal consistency, criterion validity, and construct validity with Cronbach’s alphas ranging 0.71-0.95. Conclusion: The Substance Use Risk Profile was found to be a beneficial tool to be employed in research realted to substance use disorder in Pakistan. Key Words: Adaptation, Substance use risk profile scale, Personality, Substance use disorder, Psychometric properties, Confirmatory factor analysis.